Formality in psychotherapy: How are therapists’ and clients’ use of discourse particles related to therapist empathy? - Lee, Jonathan Him Nok; Chui, Harold; Lee, Tan; Luk, Sarah; Tao, Dehua; Lee, Nicolette Wing Tung (Frontiers in Psychiatry, 2022)
Previous studies explored the preferences for therapists’ attire and office setting based on initial impressions as a reference for the formality in psychotherapy. This study examines the formality of psychotherapy by investigating therapists’ and clients’ use of discourse particles, the linguistic marker and quantifier of the formality in speech, in relation to therapist empathy in different stages of psychotherapy. Four psychotherapy sessions (representing early, mid, and late stages) each from 39 therapist-client dyads were analyzed. Trained observers rated therapist empathy in each session using the Therapist Empathy Scale. Results of multilevel modeling show that synchrony in particle usage, hence synchrony in formality, between clients and therapists is not associated with therapist empathy. Therapists’ use of particles (i.e., absolute formality of therapists) was also not associated with therapist empathy. In contrast, the relative formality of therapists plays significant roles: therapist empathy is generally observed when therapists are relatively more formal than the clients (i.e., lower relative usage of particles by the therapists when compared to the clients). However, for clients who speak formally with few particles, therapist casualness (i.e., higher relative usage of particles than the clients) at the beginning of therapy may be interpreted as therapist empathy as therapists help these clients ease into the therapeutic relationships. Our results suggest that the examination of therapists’ and clients’ use of particles across different stages of treatment may illuminate dynamic interactional styles that facilitate or hinder the psychotherapy process.